Influence of Dexamethasone on Pharmacokinetic Parameters of Cyclosporine in Rabbits - Abushammala, Issam; Zomlot, Badeaelzaman; Mosabeh, Mariam; El-Gussein, Lama (Jordan Journal of Pharmaceutical Sciences, 2021)
The present study was designed to investigate the presence of significant pharmacokinetic (PK) interaction between Dexamethasone (DEX) at different concentrations on Cyclosporine (CsA) PK parameters in healthy male rabbits. The rabbits were selected and divided into three groups: Control group (n=6) received orally CsA solution (7.5 mg/kg/day) prepared from soft gelatin capsule for five days and on the fifth day, serial blood samples were withdrawn from marginal ear vein of rabbits at different time intervals post-dosing. In the first and second groups, rabbits were given orally (7.5 mg/kg/day) CsA solution concomitantly with DEX at two doses (0.33 and 0.66 mg/kg/day), respectively. On the fifth day of administration, each test group’s serial blood samples were collected for over 24 hours as in the control group. Different PK parameters of CsA for the three groups were determined using non-compartmental analysis. It was observed that, there were statistically insignificant differences between control and test groups when co-administered with DEX at both concentrations. The present study results demonstrated that concurrent administration of DEX at both concentrations had not influenced the PK parameters of CsA.